Growth and Survival Rate Goldfish (Carassius auratus L.) in Various Natural Feed Dosage Tubifex sp. - Risdawati, Risdawati; Widiastuti, Irawati Mei (FAPETKAN UNTAD, 2021)
Goldfish (Carassius auratus L.), one of the most popular and freshwater ornamental fish to be cultivated in Indonesia. One obstacle in the cultivation of Carassius auratus L. is the high feed cost (60-70%) of the total production cost. The natural food source for fish Carassius auratus L. is Tubifex sp. which has a high nutritional content. The aim of the study was to determine the dosage of Tubifex sp. best for the growth and survival rate of goldfish (C. auratus L.). This research was conducted at the Laboratory of Water Quality and Aquatic Biology, Faculty of Animal Husbandry and Fisheries, Tadulako University for 2 month (January to March 2020). The experimental design used a Completely Randomized Design (RAL) with 5 treatments and 4 replications. The treatment in this study was the administration of silk worms with different doses (A = 6%; B = 8%; C = 10%; D = 12%; E = 14%). The variables measured included absolute weight growth, survival and water quality. Data were analyzed by analysis of variance (ANOVA), with further tests BNJ using Excel 2010 and Minitab 16 application programs. The results showed that the natural feed (Tubifex sp.) shows a significant growth in absolute weight, but has no effect on survival. The absolute growth of goldfish seeds was the highest in the feeding of Tubifex sp. with a dose of 12% of 14.82 Â± 2.76 g with a survival rate of 90.63% Â± 6.25. Water quality (temperature, pH, dissolved oxygen and ammonia) is still in accordance with the growth needs of goldfish fry.